Correlation Studies on Seed Quality, Pod and Seed Yield in Germplasm of Pea (Pisum sativum L.) - Panwar, Abhishek; Mishra, A. C.; Negi, Shivangi (International Journal of Bio-resource and Stress Management, 2018)
The present investigation was carried out during Rabi, 2014 at Research Block, Department of Crop Improvement, V. C. S. G. Uttarakhand University of Horticulture and Forestry, College of Forestry, Ranichauri Campus with 16 genotypes of vegetable pea (Pisum sativum L.) including released commercial cultivars and elite lines developed from different Institutes of India. With view to find out relationship of seed viability and seedling vigour parameters with field performance of the genotypes, the crops of all genotypes were raised in Randomized Block Design with three replications. The experimental crops were raised using recommended cultural operations for this region. Observations were recorded for days to 50% flowering, plant height at 50% flowering, number of pods plant-1, pod length, pod diameter, number of seeds pod-1, 10 pod weight, pod yield plant-1 and seed yield plant-1. Correlation studies showed pod yield per plant was positively and significantly correlated with standard germination (0.807), seed vigour index-II (0.654), seedling fresh weight (0.600) and seedling dry weight (0.597). Seed yield plant-1, highly significant and positive correlation was observed with seed vigour index-II (0.392) and seedling dry weight (0.390). It is evident that prior estimation of standard germination, seedling dry weight and seedling vigour index-II of the seed lot in any genotype could be used to predict the yield potentiality of that genotype in open field conditions and the genotypes with higher values for these seed traits could be assumed to give higher pod and seed yield.